Case report: Case series of urinary retention in young adults with severe autism hospitalized for behavioral crisis - Nollace, Leslie; Panagiotis, Drolapas; Convertini, Josephine; Grilo, Nuno; Ansermot, Nicolas; Guinchat, Vincent (Frontiers in Psychiatry, 2025)
BackgroundBehavioral regressions in low verbal patients with severe autism constitute a dramatic challenge for clinicians. A physical comorbidity burden is often involved but difficult to evidence.AimWe present five cases of patients under 30 years old (three men and two women), recently hospitalized in a specialized multidisciplinary inpatient unit, settled in Lausanne University Hospital, and for which at some point, a urinary retention contributed to the constitution of a complex behavioral picture.MethodsFor each patient, we report the individual risk factors, clinical presentation and the conditions for making the diagnosis.ResultsAs the usual guidelines for screening, management, and follow-up of urinary retentions are irrelevant in this population, we provide and discuss some recommendations: limitation of anticholinergic burden, strict application of the protocol for going to the toilet with training protocol, regularization of intestinal transit, daily bladder-scan control, and eventually use of Tamsulosin hydrochloride. These recommendations significantly improved the urinary status of our patients.ConclusionWe conclude that chronic urinary retention is probably a recurrent and unrecognized feature in many young adults with autism and challenging behaviors, reflecting the long-term impact of iatrogenic medication and requiring a specific attention.